Hydraulic Performance of Concrete Block Pavement under High Rainfall Intensities - Sedyowati, Laksni; Susanti, Eko Indah (Fakultas Teknik UB, 2019)
High rainfall intensity will generate different response on the concrete block pavement (CBP) performance. A study found that larger openings of CBP did not lead more water penetrated. In other study, larger openings can lead greater decrease in runoff velocity. The correlation between the openings, water penetration and runoff velocity has remained unclear. In this study, we investigated hydraulic performance of CBP as an impact of surface roughness condition, under high rainfall intensities, saturated sub-base layer, and various slope surfaces. We conducted experiment using a 2 m by 6 m of rectangular CBP layer with herringbone 90 and basket-weave pattern. We used a modified dye tracing method in view to monitor the surface flow velocity under various high rainfall intensities. The results showed that hydraulic performance of surface runoff in the CBP layer was more influenced by the surface roughness condition. The roughness condition was very sensitive to the change in surface configuration of the CBP. The relationship between rainfall intensity, surface slope and roughness number followed polynomial functions. A further study is required to investigate the appropriate quality of CBPs, which have high durability applied over a steep slope surface and under high rainfall intensities.